TEACHER PROFESSIONALISM IN RICHARD LAGRAVENESE’S FREEDOM WRITERS MOVIE - Sri Rahayu Astuti; Restu Arini (Indonesian EFL Journal, 2022)
Professionalism is pivotal for teachers because it influences student accomplishment and qualifies educational goals. The demeanor of professional teachers encourages students to develop what is inside them and present it to the world. Based on Socket's professional teacher theory, the study analyzes Lagravenese’s Freedom Writers movie to describe teacher professionalism through Erin Gruwell's character. To answer this problem, literature study, in-depth analysis and descriptive-qualitative methods are used. The study revealed that professional teachers' performance by Erin Gruwell contains five aspects: character, commitment to change and continuous improvement, subject knowledge, pedagogical knowledge, obligations and working relationships outside the classroom. The impact is also seen by the changes in students’ behavior from being difficult to manage to being obedient students with good achievements. Thus, teacher professionalism produces prestige for students making them able to become learners with good behavior, motivation, and academic performance.Keywords: teacher professionalism; teacher competences; student behavior; teacher education.